Analisis Kompensator Seri Menggunakan Thyristor Untuk Sistem Daya Listrik - Taupiq Rahman Siregar; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Along with the growth of society and technological improvements, the demand for electricity continues to increase. However, the development of the electric power system is not sufficient to supply the needed electrical energy. For this reason, it is necessary to regulate and manage a good electricity distribution system so that the current growth of community needs is met and has a high enough reliability. The installation failure in the electric power system cannot be avoided due to the long transmission distance. This has a major effect on the flow of power in electric power transmission resulting in a decrease in voltage and loss of electrical power. One of the ways to overcome voltage stability and improve the reliability of the electrical power system is to use a Flexible Alternating Current Transmission System (FACTS). One of the FACTS devices is the Thyristor Controlled Series Compensator (TCSC). The TCSC is installed in series with the transmission line and is used to increase the power capabilities of the transmission line. Regulating the reactance of the transmission line can be done by controlling the reactance of the TCSC so that the power flowing can be increased. After conducting a power flow study using the MATLAB 2016a PSAT toolbox software, it was found that the voltage on the Bangkinang bus was 0.9868 p.u (148.02 kV) and on the Garuda Sakti bus was 0.9637 p.u (144.55 kV). After installing the TCSC on the Riau 150 kV transmission system, the TCSC was installed on the Garuda Sakti transmission line - Balai Pungut. The installed TCSC rating is 24 Mvar. The value of the alpha parameter is 0.2 and (-0.8) radians. After installing the TCSC, voltage stability the Bangkinang bus and the Garuda Sakti bus increased to 0.99008 p.u (148.512kV) and 0.97693 p.u (146.535kV). The percentage increase is 0.4% on the Bangkinang bus, 1.15% on the Garuda Sakti bus, the average stress on the object of research has increased by 1.15%. Keywords: Electric Power System, FACTS, TCSC, Matlab R2016a toolbox PSAT